SOSIALISASI POTENSI PENGEMBANGAN TANAMAN LECI DI NEGERI HATIVE BESAR, KECAMATAN TELUK AMBON, KOTA AMBON, PROVINSI MALUKU - Hukom, Zakaria; Rehatta, Herman; Mardiatmoko, Gun; Kunu, Pieter; Talahaturuson, A.; Patti, Jogeneis; Effendy, Jollanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Lychee plants are commercial fruit plants, on Ambon Island they grow along the Negeri Hative Besar road. They are local lychee plants (Litchi chinensis Sonn Var. Amboinensis) which grow in home gardens as landscape plants and have not been commercially cultivated. This cultivar has adapted to the lowland environment, namely 5 - 400 m above sea level with rainfall of 2500-3000 mm/year, minimum temperature of 23.4-25.6°C and humidity of 82.3-87.4%. Lychee on Ambon Island is widely cultivated as a yard plant in Negeri Soya, Naku, Hatalai, Hukurila, Ema, Amahusu, Eri, Lateri, Tulehu, Hative Besar and Tawiri as well as other villages in the Lease Islands (Haruku Island, Saparua and Nusalaut), South Seram and West Seram. The yield of lychee fruit in these areas is still very low with a quality that cannot be maintained as an exotic fruit that has commercial economic value because the fruit skin cracks and its taste is sour because it has not received good praktice agrotechnology. The application of appropriate lychee cultivation technology through socialization activities, demonstrations and assistance in providing Complete Organic Liquid Plant Nutrition Landetox to lychee trees in the yards of the community in Negeri Hative Besar, Teluk Ambon sub-district, Maluku province has provided an increase in high yields with satisfactory lychee fruit quality and marketable as a promising source of income for the community.